Academic Senate Minutes 2008-12-18 - Academic Senate:::::::::
Chair Report. Correspondence. Minutes of 12/4/08 postponed. Certificate in TESOL – Approved. By-Laws amendment on Student Voting on Standing and Subcommittees – Approved. Provost Report. Vote on motion "that the Academic Senate adopt as its own the position statement of the Academic Freedom Subcommittee on SSU's Job Fair Code of Conduct and convey this proposal to the Vice President of University Affairs, Dan Condron." Approved. CFA report. Core Academic Priorities Progress Report from APC. WASC Discussion – Diversity